Post extraction pyogenic granuloma: A Case Report and Literature Review - Laila M Abdelrahim; Najat M Ghuela; Asma M Abdelrahim (Libyan Journal of Medical and Applied Sciences, 2025)
Pyogenic granuloma (PG) is a benign vascular lesion that typically appears as a tumor-like growth in the oral cavity, often resulting from an inflammatory response to minor trauma or irritation. It is characterized by rapid growth, a propensity to bleed, and is commonly found on the gingiva, tongue, and other oral tissues. It is characterized by its reactive nature rather than being a true neoplasm. Clinically, PG presents as a soft, rapidly growing mass that is has tendency to bleeding and can vary in size from a few millimeters to several centimeters. The condition is often associated with local irritation or trauma, hormonal changes, and can occur in various locations within the oral cavity, including extraction sockets, although this is rare. A literature review also indicates that pyogenic granulomas are primarily found in the gingiva but can develop in extraction sockets, especially after trauma or irritation. The pathogenesis of pyogenic granuloma is not entirely understood, but it is believed to be a reactive process to local irritants or trauma. The condition is more prevalent in females and often occurs in individuals in their third and fourth decades of life. The standard treatment involves surgical excision, which is usually curative, although laser therapy is emerging as an alternative method for removal. This report discusses the case of pyogenic granuloma in a 38-year-old breast feeding mother in extraction site in lower left back tooth region. And discusses diagnostic challenges and treatment options.